Taoísmo e Confucionismo: duas faces do caráter chinês - Cordeiro, Ana Lúcia Meyer (Sacrilegens, 2009)
This article aims to investigate the basic principle of the Taoism and Confucianism, focusing, above all, the meaning of the concept Tao in two religious traditions. The Taoism is a mystical and philosophical doctrine that exerted big influence in China along its history. The Confucianism is a joint of the thoughts, rules and social rituals practiced by Chinese elites until the fall of the imperial regime, in 1911. Taoism and Confucianism represent two innate faces of the Chinese character, the first corresponding to romantic face and the second, to classic face.